2008
DOI: 10.1902/jop.2008.080132
|View full text |Cite
|
Sign up to set email alerts
|

The Short‐Term Effectiveness of Non‐Surgical Treatment in Reducing Levels of Interleukin‐1β and Proteases in Gingival Crevicular Fluid From Patients With Type 2 Diabetes Mellitus and Chronic Periodontitis

Abstract: Non-surgical periodontal treatment was effective in reducing the levels of IL-1beta, elastase activity, and MMP-8 and -9 in GCF from diabetes and control groups. Patients with T2DM showed less reduction only in elastase activity in shallow sites compared to controls. This reduction was associated with improvement of the clinical periodontal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 44 publications
(93 reference statements)
11
77
1
3
Order By: Relevance
“…It may be suggested that the initially higher levels of PI and BOP throughout the duration of the study in the diabetic group might have had an impact on healing, as reflected by the greater PD and CAL in the diabetics. Studies evaluating the initial periodontal treatment in diabetic patients with periodontitis reported that clinical healing was parallel to that seen in systemically healthy controls in terms of PD, CAL, PI, and BOP levels [19][20][21][22][23][24][25][26]. Kıran et al [27] reported a significant decrease in CAL after non-surgical periodontal treatment at 3 months.…”
Section: Discussionmentioning
confidence: 96%
“…It may be suggested that the initially higher levels of PI and BOP throughout the duration of the study in the diabetic group might have had an impact on healing, as reflected by the greater PD and CAL in the diabetics. Studies evaluating the initial periodontal treatment in diabetic patients with periodontitis reported that clinical healing was parallel to that seen in systemically healthy controls in terms of PD, CAL, PI, and BOP levels [19][20][21][22][23][24][25][26]. Kıran et al [27] reported a significant decrease in CAL after non-surgical periodontal treatment at 3 months.…”
Section: Discussionmentioning
confidence: 96%
“…Cross-sectional baseline (Sbordone et al 1995) and longitudinal continuation study (Sbordone et al 1998 (Iwamoto et al 2001, Talbert et al 2006, O'Connell et al 2008, Aspriello et al 2011, Passoja et al 2011, lacked information about the clinical periodontal status of the subject groups (Araya et al 2003, Gomes et al 2006, Shin et al 2010 or compared groups with different clinical indices of periodontitis (Bulut et al 2001, Safkan-Seppala et al 2006, Correa et al 2008, Matsumoto et al 2009, Venza et al 2010, Surdacka et al 2011. It is possible to assume that altered local, rather than systemic, mediators may have a more important role in periodontitis; however, evidence of quantitative and qualitative differences in these mediators in patients with diabetes is very inconsistent ( Table 2).…”
Section: Cytokines and Adipokinesmentioning
confidence: 99%
“…Nos estudos de Da Cruz et al 17 foram melhorados o índice de placa em todos os tempos para diabéticos e não diabéticos após 3 meses, assim como o índice de sangramento gengival. Resultados semelhantes com respeito a essas variáveis foram encontradospor outros autores para o índice de placa 8,12,13,16,18,19,25 e índice gengival. 8,13,16,18,19 A redução significativa desses parâmetros após a terapia confirma a eficácia do controle de higiene oral e redução da inflamação gengival.…”
Section: Discussionunclassified
“…8,13,16,18,25 Em contrapartida Correa et al 16 e Da Cruz et al 17 não atingiram significância estatística para glicemia em jejum e níveis de HbA1c. Gonçalves et al 13 e Monteghavi et al 26 não encontraram resultados significativos para redução dos níveis de HbA1c o que não confirma a hipótese de que o tratamento periodontal não-cirúrgico ocasiona controle glicêmico.…”
Section: Discussionunclassified